Isolation and Pathogenic Characterization of Pigeon Paramyxovirus Type 1 via Different Inoculation Routes in Pigeons - Chang, Han; Feng, Shengyong; Wang, Yutian; Li, Fuhuang; Su, Qianqian; Wang, Bo; Du, Juan; He, Hongxuan (Frontiers in Veterinary Science, 2021)
Pigeon paramyxovirus type I (PPMV-1) causes regular outbreaks in pigeons, even poses a pandemic threat among chickens and other birds. The birds infected with PPMV-1 mainly show the pathological damage in respiratory system, digestive system and nervous system. However, there were few reports on the efficiency of the virus entering the host via routes of different systems. In the present study, a PPMV-1 strain was obtained from a dead wild pigeon in 2016 in Beijing, China. The mean death time (MDT) and the intracerebral pathogenicity (ICPI) showed that virulence of our isolate was medium. Phylogenetic analysis based on F gene sequence showed that the isolate belonged to sub-genotype VIb, Class Ⅱ, which was dominated in China in recent years. Then, we evaluated the infection efficiency of different routes. Pigeons were randomly divided into five groups of six. All pigeons were inoculated with 100 μl 106 EID50 PPMV-1 virus via intracephalic (IC), intranasal (IN), intraoral (IO), cohabitation infection (CO), and negative control (N negtive) . After infection, pathological lesions, virus shedding, body weight change, survival rate, and tissue tropism were tested to compare efficiency of different infected routes. The mortality of Group IC, Group IN, Group IO and Group CO were 100%, 66.7%, 50% and 33.3%, respectively. Weight loss in Group IC was more than the other groups, followed by Group IN and Group IO. The lesions observed in PPMV-1-infected pigeons were severe, especially in lung and instine in Group IC. Virus shed from 2 dpi in Group IC and Group IN, but the shedding rate was higher in Group IN than Group IC. The longest period was in Group CO. Tissues tropism experiment showed our isolate was wide range of tissues distribution, and the virus titer in heart and intestine of Group IC, and in brain of Group IN was higher. Our data may help us to evaluate the risk of transmission of PPMV-1.